2018
DOI: 10.1111/tid.13006
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplantation for infective endocarditis: Viable option for a limited few?

Abstract: Active infection in the recipient is considered a relative contraindication for solid organ transplantation. However, heart transplantation (HT) can be curative in patients with ventricular assist device infections. For patients with infective endocarditis (IE), valve replacement is part of the management strategy based on emergent, acute, or elective indications. HT has been utilized as an uncommon and sporadic treatment option for carefully selected patients with refractory or recurrent IE after all other su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…3 HT is the utmost controversial topic, due to the need for immunossupression. 4,5 Although guidelines support its use in extreme cases, there is little experience on the field and recommendations are scarce, being rarely performed in IE. 1,4,5 The patient had recurrent PVIE with major cardiac tissue destruction, making surgery unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…3 HT is the utmost controversial topic, due to the need for immunossupression. 4,5 Although guidelines support its use in extreme cases, there is little experience on the field and recommendations are scarce, being rarely performed in IE. 1,4,5 The patient had recurrent PVIE with major cardiac tissue destruction, making surgery unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, HT as salvage therapy for IE remains a rare indication. There are no robust data defining criteria for HT in patients with refractory IE, while the ESC guidelines mentioned HT as a measure of last resort…”
Section: Discussionmentioning
confidence: 99%
“…Vikram and Murphy have recently proposed general criteria and suggested that, with the availability of effective antibiotic therapy in the post‐transplantation period, HT could be taken into account as a measure of last resort in patients with younger age, without significant comorbidities with persistently negative blood cultures at the time of HT, and without major embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Society of Cardiology suggests it as a last resort in highly vetted candidates . A recent literature review aggregated all published cases—a total of 19—and proposed criteria for evaluating IE patients who may benefit from heart transplant . However, there remains a paucity of literature on this approach, much less in patients with B henselae IE.…”
Section: Discussionmentioning
confidence: 99%